Rare bird documentation form for Peregrine Falcon at Otter Creek Marsh, 1984 - Kent, Thomas H. (Thomas Hugh), 1934-et al (1984)
Rare bird documentation form for a Peregrine Falcon at Otter Creek Marsh in Tama County, IA on May 14, 1984. Epson - sheet feed